Banking and Wealth Creation for Stakeholders in Cameroon: An Exploratory Study - Sunday Agbor Mbu; Ayuketang Nso Maurice (European Scientific Journal, ESJ, 2022)
This paper focuses on surveying the association between banking and wealth creation for customers, bankers, and owners of financial institutions in Cameroon. Questionnaires were administered using a random sampling technique, and this formed the principal instrument for data collection for the study. Eighty-five (85) questionnaires were sent out but only fifty-four (54) were returned and used for the analysis. Chi-square and Pearson Correlation were preferred and used to analyse the data for expediency. Results show no relationship between banking and wealth creation for customers in Cameroon. There is a certain claim that bankers and owners of financial institutions are wealthier than customers who provide the much-needed deposits that are used for investments. These results mean that customers bank not because they want to create wealth but because of the transaction services, safety, and security that financial institutions offer them.